THE EFFECT OF SCHOOL LEARNING FACILITIES ON STUDENTS’ LEARNING MOTIVATION AT SDN 091302 PEMATANG PANEI - Elma Cerinda Sianipar; Lasria Margaretha Simalango; Rika Budiani Br Manik; Riska Sianturi; Citra Hotmauli Viavanni Br. Simbolon; Herman Herman; Melvin M. Simanjuntak (Jurnal Scientia, 2023)
This research was conducted with the aim of analyzing how the influence of learning facilities and facilities on students' learning motivation. This type of research is a qualitative research using a descriptive approach. Data collection techniques through interviews. FGD (focus group discussion) and documentation. In this study, the authors also used the literature review method which aims to collect and extract information from previous research and analyze some of the descriptions of experts contained in the text. From this study, the authors obtained the results that learning facilities and equipment were able to increase students motivation in learning, because the more adequate the learning facilities, the deeper the students’ knowledge so that students motivation towards learning would grow as well as students' performance and ability to understand would increase'.